Bis-indolylmethane Derivatives as A Potential Colorimetric Sensor for Chromium Ion Detection in Water (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
Contamination of water with chromium ions is a significant concern due to its potential adverse effects on human health and the environment. In addition, it is also hazardous to biological systems and can cause a variety of human diseases. Hence, an efficient and reliable detection method is needed to overcome this issue. In this study, a colorimetric sensor method based on bis-indolylmethane (BIM) was developed to evaluate its ability as a heavy metal ionophore with the existence of H-bonding interactions between the indolic N–H groups and the chromium ion. In the study, two bis-indolylmethane derivatives compounds were synthesised using acetic acid as the catalyst via the condensation reaction between 5-bromoindole and benzaldehyde derivatives. The synthesised compounds were then characterised using three types of spectroscopic analysis, which are 1H and 13C NMR, FT-IR and UV-Vis to determine the structural information and to confirm the formation of the bis-indolylmethane derivatives produced. Finally, colourimetric sensor development was conducted involving metal screening with Cr3+ ion by colourimetric sensing analysis, and compound 1 was shown to have the most intense colour change, hence having the highest possibility of interaction or bonding with the Cr3+ ion. A further binding interaction study was conducted using UV-Vis titration analysis between compound 1 and Cr3+, proving the binding ability and capability of the synthesised BIMs as a heavy metal ion sensor. The successful development of this sensor will have wide-ranging applications in environmental monitoring, water treatment, and public health. Additionally, it can be employed by regulatory agencies, industries, and researchers, especially to ensure the safety and quality of water resources. By enabling quick detection of chromium ions, this sensor will contribute to the preservation of human health and the environment.